2003
DOI: 10.1016/s0020-1383(02)00193-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of traumatic brain injury amongst children admitted to hospital in one health district: a population-based study

Abstract: Article Title: Prevalence of traumatic brain injury amongst children admitted to hospital in one health district: a population-based study AbstractThere is a dearth of information regarding the prevalence of brain injury, serious enough to require hospital admission, amongst children in the United Kingdom. In North Staffordshire a register of all children admitted with traumatic brain injury (TBI) has been maintained since 1992 presenting an opportunity to investigate the incidence of TBI within the region in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 10 publications
7
94
1
2
Order By: Relevance
“…In a retrospective study, Liu et al [11] reported a mortality rate of 22.70% in 66 patients falling from 6 meters or above. Hawley et al [23] reported a significantly increased mortality in patients falling from 6 meters and reported a threshold of 6 meters for fatal fall heights for individuals below 15 years of age. In our study, compared with mortality of falls from 3 m or below, the mortality rates associated with falls from 3-6 m, 6-10 m, and 10 m and above were increased 5, 6.50, and 13 times, respectively (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, Liu et al [11] reported a mortality rate of 22.70% in 66 patients falling from 6 meters or above. Hawley et al [23] reported a significantly increased mortality in patients falling from 6 meters and reported a threshold of 6 meters for fatal fall heights for individuals below 15 years of age. In our study, compared with mortality of falls from 3 m or below, the mortality rates associated with falls from 3-6 m, 6-10 m, and 10 m and above were increased 5, 6.50, and 13 times, respectively (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…No que concerne à gravidade do trauma, segundo a escala de coma de Glasgow, observamos nos resultados atuais a preponderância do TCE leve (63,8%). O predomínio de vítimas com trauma leve em unidade de emergência é salientado em estudos anteriore s , independente da faixa etária analisada, podendo a maioria ser dispensada de um tratamento neurocirúrgico específico 10,15,16 .…”
Section: Discussionunclassified
“…TBI has become a major global health epidemic and is the most common cause of death and disability for those aged 45 and younger (Caro, 2011;Langlois, Rutland-Brown, & Thomas, 2006;Ontario Brain Injury Association, 2005;Hawley, Ward, Long, Owen, & Magnay, 2003). TBI accounts for 1.4 million deaths, hospitalizations, and emergency department visits in the United States each year (Langlois et al, 2006), and the United Kingdom has an estimated incidence of 300 per 100,000 population for all age groups (Hawley et al, 2003).…”
Section: Traumatic Brain Injury and Client-centered Carementioning
confidence: 99%
“…TBI accounts for 1.4 million deaths, hospitalizations, and emergency department visits in the United States each year (Langlois et al, 2006), and the United Kingdom has an estimated incidence of 300 per 100,000 population for all age groups (Hawley et al, 2003). Incidence rates peak in the young adult population because of motor vehicle collisions, and rates then increase among older adults because of falls (Langlois et al, 2006).…”
Section: Traumatic Brain Injury and Client-centered Carementioning
confidence: 99%